Closed Shell Iron(IV) Oxo Complex with an Fe-O Triple Bond: Computational Design, Synthesis, and Reactivity - Andris, Erik; Segers, Koen; Mehara, Jaya; Rulíšek, Lubomír; Roithová, Jana (Angewandte Chemie (International ed. in English), 2020)
Iron(IV)-oxo intermediates in nature contain two unpaired electrons in the Fe-O antibonding orbitals, which are thought to contribute to their high reactivity. To challenge this hypothesis, we designed and synthesized closed-shell singlet iron(IV) oxo complex [(quinisox)Fe(O)]+ (1+ ; quinisox-H=(N-(2-(2-isoxazoline-3-yl)phenyl)quinoline-8-carboxamide). We identified the quinisox ligand by DFT computational screening out of over 450 candidates. After the ligand synthesis, we detected 1+ in the gas phase and confirmed its spin state by visible and infrared photodissociation spectroscopy (IRPD). The Fe-O stretching frequency in 1+ is 960.5 cm-1 , consistent with an Fe-O triple bond, which was also confirmed by multireference calculations. The unprecedented bond strength is accompanied by high gas-phase reactivity of 1+ in oxygen atom transfer (OAT) and in proton-coupled electron transfer reactions. This challenges the current view of the spin-state driven reactivity of the Fe-O complexes.
Keywords: iron oxo complexes; ion spectroscopy; ligand design; spin state